2003
DOI: 10.1590/s0036-36342003000600005
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia de micosis en pacientes inmunosuprimidos de un hospital regional de la Ciudad de México

Abstract: Patricia Manzano-Gayosso, M en C, (1) Rocío López-Alvarez, QFB, (2) Elva Bazán-Mora, Biól,Rubén López-Martínez, MC.(1) AbstractObjective. To isolate and identify the fungi in specimens collected from immunocompromised patients seen in Mexico City hospital, and to assess their association with mycosis. Material and Methods. A total of 268 specimens from 108 patients were processed for mycological study, including direct examination, smears, cultures, and microcultures in specific media, in addition to biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…This frequency is equal to that reported by other Mexican authors that have used similar methodology 9 . In a study carried out by Hernández et al 26 , using phenotypycal methods with different biological products, a frequency of C. parapsilosis isolation of 68.6% was reported, followed by C. albicans (8.6%) 26 . In a 3-year surveillance study (2004)(2005)(2006)(2007) with Candida isolates obtained from patients of hospital centers from Monterrey (Mexico), and using phenotypical studies, González et al 27 reported C. parapsilosis as the species most commonly isolated from blood (37.9%), followed by C. albicans (31.9%), C. tropicalis (14.8%) and C. glabrata (8%), mainly in pediatric population who were catheter carriers.…”
Section: Discussionmentioning
confidence: 98%
“…This frequency is equal to that reported by other Mexican authors that have used similar methodology 9 . In a study carried out by Hernández et al 26 , using phenotypycal methods with different biological products, a frequency of C. parapsilosis isolation of 68.6% was reported, followed by C. albicans (8.6%) 26 . In a 3-year surveillance study (2004)(2005)(2006)(2007) with Candida isolates obtained from patients of hospital centers from Monterrey (Mexico), and using phenotypical studies, González et al 27 reported C. parapsilosis as the species most commonly isolated from blood (37.9%), followed by C. albicans (31.9%), C. tropicalis (14.8%) and C. glabrata (8%), mainly in pediatric population who were catheter carriers.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of invasive candidiasis has increased during the past few years (Hernandez-Hernandez 2003, Godoy et al 2003, Colombo et al 2006, Tortorano 2006. C. albicans is the most common fungal pathogen caus-ing endovascular infections, such as IE, vascular catheter sepsis and infections of vascular prostheses (Chang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Esta frecuencia es igual a la reportada por otros autores mexicanos que han realizado una metodología similar 9 . En un estudio llevado a cabo por Hernández, et al 26 , a partir de diferentes productos biológicos y utilizando métodos fenotípicos, se reportó una frecuencia de aislamiento de C. albicans del 68.6%, seguida de C. parapsilosis (8.6%) 26 . En un estudio de vigilancia de 3 años (2004-2007) con aislados de Candida spp.…”
Section: Discussionunclassified